Synergy of Risk Handling: Shaping Financial Performance in Sharia Cooperatives - Sari, Yuli Indah; Widhyasti, Sasti Anjana (IQTISHADIA, 2025)
Sharia cooperatives in Indonesia remain vulnerable to various risks, particularly those that affect their financial performance. Therefore, this study aims to examine the influence of risk management in greater detail through the dimensions of identification, monitoring, and mitigation, as well as the role of Islamic governance in shaping the financial performance of sharia cooperatives. The sample was determined using purposive sampling and the Slovin method. Out of 118 cooperatives under Baitul Maal wat Tamwil Bina Ummat Sejahtera (BMT BUS), 105 met the eligibility criteria for analysis using Partial Least Squares (PLS). The findings reveal that risk identification, risk monitoring, risk mitigation, and Islamic governance have a significant positive impact on the financial performance of sharia cooperatives. These results provide valuable insights for cooperative managers, highlighting the importance of strengthening risk management systems—particularly in identification, monitoring, mitigation, and governance—to safeguard financial performance against potential losses arising from risks. This study offers original insights by providing a detailed exploration of risk management and Islamic governance within the context of sharia cooperatives in Indonesia.